Atividade antimicobacteriana, antibiofilme e avaliação da toxicidade in vitro de complexos metálicos do sulfametoxazol - Siqueira, Fallon dos Santos (2018)
Rapidly growing mycobacteria (RGM) are opportunistic microorganisms, found in the environment, that can cause both local and disseminated infections. RGM can form structured communities that adhere to solid biotic or abiotic surfaces, characterizing one of their most powerful survival mechanisms, biofilms. Biofilms are considered important sources of infections on biomedical surfaces, and most infections involving biofilm formation are associated with medical device implants such as catheters and prostheses. Therefore, there is an urgent need for new antimicrobial compounds that can combat microbial resistance associated with the formation of RGM biofilms. In recent years, the coordination of metals to classic antimicrobials have shown excellent activity against a variety of microorganisms in planktonic form. In this context, this work aimed to evaluate, for the first time, the antibiofilm action of sulfamethoxazole complexed with Au, Cd, Cu, Ni and Hg on Mycobacterium abscessus (ATCC 19977), Mycobacterium fortuitum (ATCC 6841), Mycobacterium massiliense (ATCC 48898) and six clinical isolates of RGM, as well as to evaluate their safe through cytotoxic assays. Different profiles of susceptibility to drugs used in the clinic and to new compounds were determined in our study and in our results it was demonstrated that sulfamethoxazole derivatives complexed with metals showed, in the great majority of cases, activity superior to that of free sulfamethoxazole and other drugs in inhibiting the growth of RGM. The results demonstrate potentiation of the novel compounds in inhibiting the formation and destruction of biofilms of RGM. The antibiofilm activity of gold-complexed sulfamethoxazole, which was able to completely inhibit biofilm formation, is clearly pronounced. In adittion, this compound had the capacity to destroy the biofilm at all concentrations tested. All cytotoxic data are suggestive that the majority of sulfamethoxazole metallic derivatives are antimicrobial alternatives as well as safe molecules which could be used as potential therapeutic agents for bacterial and biofilm elimination.